Girder deflection for lifting load / Mustapha Kamil Husen Abdul Kadir - Mustapha Kamil Husen , Abdul Kadir (2017)
This study aim is to investigate the maximum girder deflection and propose methods to reduce the deflection based on the simulation and calculation conducted on the crane girder. The crane girder deflection studies by previous researchers have not used an actual crane deflection as a guideline. Furthermore, the crane deflection is being control by modeling a dynamic control system integrated on the cane functionality. Thus, to investigate the maximum girder deflection, an equation was derived based on principle of deflection on simply supported beam. Besides that, a 3D crane girder was modeled by the used of Solid Work software and run a finite element analysis by using Ansys software. Based on the observation of girder deflection, a relationship between calculated girder deflections, simulated girder deflections and actual girder deflection are built on the basis of error percentage among these results. As results, the crane girder deflection can be reduced by more than 10% if reinforcement added inside the girder structure. The reinforcement must cover and being layout throughout the crane structure to work at its best regardless of horizontal or vertical direction. The difference between the actual crane deflections with the calculated girder deflection is more than 10% which indicate that girder deflection does not represent the crane deflection in absolute term. However, form the observation of the stress behavior analysis on the crane girder, the areas which are affected once the girder deflected now can be identified. These areas are bottom flange, top flange and girder edge which can be modified or improvised to reduce the crane as well as girder deflection further. The implications of this study contribute to achieve better crane girder design in the industrial market as well as able to prolong the crane operation life span.